Effects of Rudder and Blade Pitch on Hydrodynamic Performance of Marine Propeller Using CFD - Quang Pham Ky; Van Hung Phan; Cong Nguyen Chi; Tung Trinh Xuan (Polish Maritime Research, 2022)
The use of computational fluid dynamics (CFD) to predict internal and external flows has risen dramatically in the past decade. This research aims to use the commercial software, ANSYS Fluent V.14.5, to illustrate the effects of the rudder and blade pitch on the hydrodynamic performance of the marine propeller by experimenting with propellers and rudders of the M/V Tan Cang Foundation ship, which has designed conditions as follows: diameter of 3.65 m; speed of 200 rpm; average pitch of 2.459 m; boss ratio of 0.1730. Using CFD, the characteristic curves of the marine propeller and some important results showed that the maximum efficiency of the propeller is 0.66 with the open water propeller and 0.689 with the rudder‒propeller system at the advance ratio of 0.6. The obtained outcomes of this research are a significant foundation to calculate and design an innovative kind of propulsion for ships with high performance.